Rapid synthesis of nc-Si/a-SiNx:H QD thin films by plasma processing for their cost effective applications in photonic and photovoltaic devices. Issue 78 (26th August 2015) - Das, Debajyoti; Sain, Basudeb
<x xml:space="preserve">Abstract</x> A rapid and single step synthesis of nc-Si/a-SiNx:H QD thin films has been made possible from a (SiH4 + NH3) gas mixture, with the advent of high density low pressure planar inductively coupled plasma processing.